2012
DOI: 10.2174/1874613601206010232
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Lifetime HIV Testing in Texas by Race/Ethnicity

Abstract: Introduction:In United States, roughly 1/5 of all HIV infected persons remain undiagnosed. Because HIV testing is critical to improve prevention efforts, more research is needed to understand the characteristics of individuals who get tested for HIV.Methods: This secondary analysis of the 2010 Texas Behavioral Risk Factor Surveillance System used data from 9,744 respondents between 18-64 years of age to evaluate the relationship between demographic characteristics (gender, race/ethnicity, age, area of residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…12,[15][16][17][18] Among African Americans specifically, having had an HIV test has been associated with female gender, 19 being widowed or separated (vs. married), 20 prior diagnosed sexually transmitted infection, 19,21 recent healthcare utilization, 22 healthcare provider recommendation, 22 and being US-born (vs. foreign-born). 23 In qualitative research, African Americans suggested that specific cues to action (i.e., a stimulus, such as an experience, that triggers the decision to change health behaviors 24 ), including knowing someone living with HIV and perceiving high personal HIV risk from past behaviors, may lead to a greater readiness for HIV testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,[15][16][17][18] Among African Americans specifically, having had an HIV test has been associated with female gender, 19 being widowed or separated (vs. married), 20 prior diagnosed sexually transmitted infection, 19,21 recent healthcare utilization, 22 healthcare provider recommendation, 22 and being US-born (vs. foreign-born). 23 In qualitative research, African Americans suggested that specific cues to action (i.e., a stimulus, such as an experience, that triggers the decision to change health behaviors 24 ), including knowing someone living with HIV and perceiving high personal HIV risk from past behaviors, may lead to a greater readiness for HIV testing.…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, HIV testing may be impeded by greater perceptions of HIV stigma, for example, because individuals may fear that people who are not accepting of HIV would discriminate against them if they are found to be seropositive. 25 Among Latinos, prior HIV testing has generally been associated with female gender, 20,26 higher education level, [26][27][28] higher income, 26 older age, 20,27 being divorced (vs. married), 20 and recent or regular healthcare utilization. [28][29][30] Lack of testing is associated with undocumented residency status and being foreignborn, 26,31 perhaps because of a reluctance to interact with formal systems such as healthcare or concern about being reported to government officials.…”
Section: Introductionmentioning
confidence: 99%
“…These variables are retained in our analyses, as prior empirical and epidemiological research show that individual level differences among these variables are associated with HIV testing (4447). Additional predisposing variables for substance abuse (specifically, level of alcohol use), mental health status in the past 30 days (feeling sad, nervous, restless, hopeless, effort, worthless), living condition (ever spending more than 24 hours on the streets, shelter, jail or prison), and housing arrangement were also included in our analyses because they are specifically relevant for vulnerable subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Low family income, being uninsured, and forgoing medical care, have been identified as risk factors for inadequate access to preventive health care (4850). Further, research has shown that region is an important factor when accessing HIV testing services, and that individuals living in urban settings are more likely to test for HIV (44, 51). Need factors in our analyses consist of individuals’ perceived and evaluated need for interactions with health service providers.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this lack of disclosure is due to true lack of knowledge regarding HIV risk or to reluctance to acknowledge this risk, to themselves, or to blood centers is unknown. This demonstrates that high‐risk behavior does not always translate into voluntary testing; and, although perception of risk may be an important predictor of testing, it does not necessarily lead to risk avoidance, and risk denial remains a major barrier to testing . Interestingly, HIV‐negative blood donors with reported sexual risk comprised the only group in which females did not demonstrate an increased likelihood of having been tested previously for HIV.…”
Section: Discussionmentioning
confidence: 99%